Challenges of tuberculosis prevention through early detection of latent tuberculosis infection in new immigrants to the State of Kuwait - Al-Harbi, Adel Mohanna (The University of Edinburgh, 2012)
Introduction: Despite management advances worldwide, tuberculosis still remains a serious uncontrolled disease. The absence of either a ‘gold’ standard diagnostic test, or a conventional rapid ‘reference’ laboratory test for asymptomatic Mycobacterium tuberculosis (MTB) carriers complicates disease control. Through mandatory screening of high-risk groups, early diagnosis of latent tuberculosis infection (LTBI) cases allows recognition and better control of the tuberculosis pandemic. Materials and Methods: The current tuberculosis screening guidelines as recommended by the World Health Organization, chest X-ray and tuberculin skin test were assessed and revealed rises in TB morbidity and fatality trends in the Kuwait population (low incidence country). In order to evaluate options for LTBI diagnosis, the current work implemented a 4-month prospective, observational, repeated-measure and randomly implemented survey on 180 new immigrants to Kuwait using a structured risk factor questionnaire whilst, simultaneously evaluating the performance of the two standard diagnostics (chest X-ray and tuberculin skin test) with the new biomarker interferon gamma release assays (T-SPOT .TB test and QuantiFERON Gold In-Tube test (QNF-GIT)); which detect the release of interferon gamma (INF-γ) released from sensitization to specific MTB antigens. Results: Associations between various epidemiological risk factors - such as socio-demographic status, smoking and environmental exposure-contact - were associated in the laboratory diagnosed LTBI participants. Positive identification of LTBI prevalence detected by two radiologists was 10.1% having ‘moderate’ inter-reader agreement (Kappa = 0.505), compared to no positives being detected by three pulmonologists. TST results were negative (less than 10-mm ‘cut-off’) even in the 86.1% Bacillus Calmette-Guérin vaccinated expatriates. Estimated LTBI using QNFGIT was 28.3% compared to 41.1% positive T-SPOT .TB test. Both interferon gamma assays revealed concordant ‘abnormal’ results in 26.1% with ‘good’ agreement (kappa = 0.627). Conclusion: Detection of latent tuberculosis infection can be facilitated by introducing evidence-based diagnostic classification depending on history taking of epidemiological-related risk factors and chest X-ray plus either interferon gamma assays.
Keywords: tuberculosis; latent tuberculosis infection; TST; IGRA